OP0019 Osteoarthritis, Drug Use and Risk of Cardiac Ischaemic Events: A Case-Control Study. (9th June 2015) - Pontes, C.; Morros, R.; Marsal, J.R.; de Abajo, F.; Castillo, J.R.; Rios, J.; Carné, X.; Du Souich, P.
Abstract : Background: Recent controversies on the safety profile of drugs used to treat osteoarthritis (OA) have led to changes in clinical guidance for management (1). Objectives: To describe associations between the use of different OA drug therapies and the risk of cardiac ischemic events (CIE). Methods: We conducted a nested case-control study within a cohort of patients with clinically diagnosed OA (according to ICD10 codes in the SIDIAP database of primary care records for over 5 million people in Catalonia, Spain (2)). Cases were identified in the period between 2008 and 2012 through ICD10 codes of cardiac ischemic events (CIE) (AIM or unstable angina, fatal or not) and cross-checked with hospital discharge diagnosis; 3 controls without CIE were matched to each case by sex, age (±5 years), area and year (±2 years) of first diagnosis of OA. Data were linked with pharmacy invoicing information, encrypted and extracted for analysis. Exposure to NSAIDs, SYSADOAs, opioids, paracetamol and metamizole were analysed. Adjusted multivariate conditional logistic regression models were fitted to estimate odds ratio (OR) for CIE according to drug use. Results: We studied 5663 cases and 16989 matched controls. Cases had more morbidity and cardiovascular risk factors, but similar characteristics for OA and joint involvement. Significantly increased risks (OR 95%CI) were observed related to the use of non-selective NSAIDs (1.10 (95%CI 1.01 to 1.19)), in particular for diclofenac (1.16 (1.07 to 1.25)) and naproxen (1.14 (1.01 to 1.29)), and for opioid analgesics (1.13 (1.04 to 1.24)). SYSADOAS, paracetamol and metamizole showed no significant associations with CIE. Conclusions: In patients with OA, non-selective NSAIDs (diclofenac, naproxen) and opioid analgesics are associated to an increased risck of CV events. This should be considered for the management of OA patients with a high cardiovascular risk profile. References: National Institute for Health Care and Excellence. Osteoarthritis care and management in adults. National Institute for Health and Care Excellence (United Kingdom), 2014. www://www.nice.org.uk/guidance/cg177/resources/guidance-osteoarthritis-pdf (accessed 25th January 2015). Bolíbar B, Fina F, Morros R et al. SIDIAP database: electronic clinical records in Primary Care as a source of information for epidemiologic research. Med Clin (Barc) 2012;138(14):617-21. Acknowledgements: The study was funded by Bioibérica S.A. Disclosure of Interest: None declared